The causal relationship between self determination and academic motivation among high school students in Banda Aceh - Ibrahim, Hasniza; Romar, Rahmi; Siregar, Irma Yanti (Faculty of Tarbiyah and Teacher Training of IAIN Padangsidimpuan, 2023)
This cross-sectional study purpose is to examine both of the self-determination and academic performance - hypothesized to be a multidimensional construct. Another purpose was to examine the relationship between students’ self-determination and their academic motivation. The sample consisted of 300 senior high school students from 5 selected schools in Banda Aceh, Indonesia. The data was collected using a self-reported of 21-item questionnaire measuring students’ self-determination and academic motivation. Confirmatory Factor Analysis procedures confirmed the structure’s measurement validity. SEM fit statistics indicated strong influences of self-determination on academic motivation. The results confirmed the study’s hypotheses regarding the multidimensionality of SDT and academic performance, the adequacy of the measurement model of Self-Determination Theory (SDT) and its strong positive role in influencing academic motivation. The results of the study supported and extended the results of previous work on STD. The study also found evidence that students’ self-determination is a valid and reliable multidimensional construct. The findings are useful in making evidence-informed the important of self-determination on students’ personality development and their motivation. This research is also significant for its contribution towards students’ academic motivation in school before they further their study in higher learning education.